The compensation claim of the criminal offences under the law of the United Arab Emirates - Alshamsi, Hamad Ali Mohamed Mejearin (2023)
This study deals with the subject of civil lawsuit arising from a criminal offence, or what is known as the lawsuit for compensation in a criminal offence. The compensation suit is a suit filed by the victim of the crime to redress the damage inflicted on him because of the violation of his right. The Criminal Procedures Law of the United Arab Emirates No. (35) of 1992 AD and its amendments, through its articles and texts, regulate the procedures for filing the lawsuit and the consequences of the civil lawsuit arising from the criminal offence. The problem was that the UAE Criminal Procedures Law did not stipulate in its articles the rights of the person affected by the crime, i.e., the victim, or the mechanism that should be relied upon to claim compensation before the competent court due to this crime. In addition, the law did not indicate the legal reason for the civil action that should be relied upon when filing a compensation claim before the competent court. The study objectives are to identify the legal controls applied to traditional crimes in the Emirates, to study the statement of victims' rights to compensation for damage from the crime, and to examine the position of international law regarding compensation for criminal damage. This study will primarily benefit judges, lawyers, prosecutors and individuals affected by criminal offences. Adopting a qualitative method, the researcher used the analytical descriptive approach of the laws related to the subject of the research together with the comparative approach to reach the objectives. The finding indicates that the legal basis for the civil lawsuit is the damage caused by the crime, and anyone who sustained damage from it may claim civil rights during the investigation into the case. In the end, the study recommended the UAE legislator enact relevant provisions that clarify certain criteria for persons affected by the crime and entitled to claim compensation.